Upaya Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran IPS melalui Metode Outdoor Study - Triyadi Haryanto; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
Instilling social values in students is a very urgent concept, because the social studies concept examines how social attitudes, social relationships and social behavior must be carried out by students in their lives. In social studies learning, learning tools and learning elements are needed, for example teacher elements, objectives, materials and facilities as well as methods which are not an easy task to be able to transform social studies values in students. All existing elements must be packaged and arranged completely so that the learning process is interesting for students, is of higher quality and learning objectives can be achieved. In reality the teacher's role and students' enthusiasm for social studies learning, there are still many problems, including 1) teachers carry out more teaching and learning activities in the form of lectures, 2) the dominance of the expository method, 3) the growth of a Verbalistic Learning Culture, 4) Teaching Centered on Textbooks (Textbook Centered), 5) Teachers who are still transferring of Knowledge. Conditions like this cause social studies to be a boring, boring subject (low student motivation) so that social studies subjects are underestimated by students which in the end mastery of subject matter by students, the percentage is small and the value of social studies lessons is low. Based on this background, it is important to study why social studies teachers need to innovate learning by applying learning methods outside the classroom (outdoor study)? how do social studies teachers apply learning methods outside the classroom (outdoor study) so as to increase students' learning motivation?. This study is a literature study. This study was conducted by analyzing the literature related to social studies learning problems and learning methods that are able to activate students in learning. The data analyzed are articles from accredited national journals, books and other relevant sources. learning activities outside the classroom (outdoor study) can be one solution to improve student learning in social studies learning by looking directly at phenomena which of course must be related to the topics the teacher teaches. The outdoor study method is a learning activity outside the classroom or school that aims to concretize and at the same time link all students' conceptual understanding of the subject matter with the natural environment and actual phenomena.